Semantic Analysis in Understanding and Maintaining Betawi Cultural Identity Through the Bikin Rume Traditional Ceremonial Process - Putri, Olivia Megantari; Siregar, Iskandarsyah; Rachmawati, Kurnia (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2024)
This research analyzes the meaning of the Traditional Ceremony Process of Making Rume and the Existence of the Betawi Language. The lack of knowledge regarding Betawi Culture in today's society has sparked the enthusiasm of researchers to research this object. The aim is to know and understand the meaning of the Bikin Rume Traditional Ceremony Process and the existence of the Betawi language. The theories used in this research are Semantic theory and supporting theories of Cultural Anthropology. The method used in this research is qualitative. This research uses observation techniques (interviews) and questionnaires (questionnaires). The observation technique is a data collection technique using in-depth interviews. The questionnaire technique (questionnaire) is a list of questions related to the problem being studied. The results obtained are the meaning of the Traditional Ceremony Process of Making Rume and the Existence of the Betawi Language.